論健康保險之保前疾病、追溯保險與被保險人之善意 ― 相關實務見解綜合評析 Pre-existing Conditions in Health Insurance, Retrospective Insurance and Good Faith – Comments on Relevant Court Rulings - 葉啟洲 Chi-Chou Yeh (Kējì Fǎxué Pínglùn, 2009)
依照保險法第127條，健康保人對於被保險人在訂約時已經存在的疾病不負保險責任。所以如果被保險人帶病投保，保險人通常拒絕給付保險金。不過，許多法院判決表示，如果訂約時該疾病無外觀上可見之症狀，而被保險人並不知道自己罹患疾病者，保險人不得免責。依照判決內容及文獻說明來看，此項見解似乎是以同法第51條第1項（追溯保險）為推論依據。但在我國法上，疾病即為健康保險的保險事故，對於訂約前已經發生的保險事故，如果契約雙方當事人並未約定將承保期刊提前，似乎不能以追溯保險之原則使保險人對該項疾病負責，以追溯保險的要件來限制保險法第127條之適用，似與該條的規範目的不符，亦有違反保險法契約對價平衡原則之虞，並不妥當。 According to Article 127 of Insurance Act, the provider of health insurance is not liable for any illness that existed before the contract is formed (pre-existing conditions), Hence, in a majority of cases, the insurers would deny the insured benefit payments based on Articles 127 or similar terms in the insurance contracts. However, a number of courts have rules that, if the insured is unaware of such pre-existing conditions because the illness has no symptoms that can be observed based on appearances, then the insurer is still liable. The basis of this judgment seemingly rests on the retrospective insurance provision in Article 51(a) of Insurance Act. Nevertheless, illness itself is an insured risk under health insurance, so without the insurer’s prior and explicit consent to extend coverage period retrospectively, it seems to be unfounded to hold the insurer liable for pre-existing conditions based on the retrospective insurance doctrine. To restrict the application of Article 127 with the retrospective insurance doctrine contradicts the intention of the legislature and the principle of equivalence.